PANORAMA OF THE SCIENTIFIC PRODUCTION OF AZUKI BEANS IN 10 YEARS - dos Santos Oliveira, Andréa; Tatiana de Almeida, Tanismare; Pereira Valero, Lucas (Journal of Interdisciplinary Debates, 2024)
Azuki bean (Vigna angularis), belonging to the Fabaceae family, is one of the most traditional crops in East Asia. It is widely consumed in Japan in dishes such as porridge, soups, cakes, pastries, and mixed with rice. Rich in fiber, magnesium, potassium, calcium, and folic acid, azuki beans contain approximately 55% starch. In Brazil, this legume is still relatively unknown, with little information available on its agricultural production. This study aims to analyze and quantify the availability of scientific articles on azuki beans, both at the national and international levels, based on publications from 2012 to 2022. The analysis period it covered the months of August to October 2022. The descriptor “Adzuki Beans” yielded the highest number of publications, with 2021 being the year with the largest volume, totaling 73 articles. In contrast, the descriptor “Feijão Azuki” showed a significantly lower number of articles, with only three publications in 2015. The Web of Science database had the highest number of published articles, totaling 488 publications during the analyzed period.